LMD On-board Equipment Based on Beidou Navigation and 5G Communication Technology - LIU Jianlin; XIAO Lizhi; TANG Zilin (Kongzhi Yu Xinxi Jishu)
With the popularization and application of LKJ monitoring and management device (LMD) in railway system, its limitations in reliability of positioning and timing, robustness of train-ground data transmission, scalability of system functions and so on are increasingly apparent. This paper puts forward a design scheme for the new generation LMD on-board equipment, which can realize reliable positioning of the train under weak satellite signal or masking scene through the third generation Beidou satellite navigation technology and multi-position source fusion technology, and adopts multi-clock source review technology to avoid the problem of accidental timing errors and improve the reliability of timing. The scheme also combines 5G communication technology, adopts dual-mode design to realize fast switching between 5G network and GSM-R private network, and the master control and communication decoupling strategy to improve the reliability of wireless communication, and solves the problem of long delay and even system downtime caused by long time-consuming recovery of vehicle-ground communication disconnection of the existing equipment. The equipment can adopt open architecture design, which improves the functional extendibility, and realizes LKJ wireless data replacement function by integrating the LKJ replacement unit. Test results show that, compared with the existing LMD on-board equipment, the designed LMD on-board equipment can be fully compatible with the existing functions, realize the accurate positioning and timing in semi shaded scenes such as stations and garages, improve the wireless communication performance by seven to ten times, and the expanded wireless data replacement function can save the production and operation man-hours of railway electrical services about 81%, so as to meet the development requirements of railway informatization for LMD system in the future.